2007
DOI: 10.1007/s00436-007-0630-8
|View full text |Cite
|
Sign up to set email alerts
|

Oligopeptidase B from Leishmania amazonensis: molecular cloning, gene expression analysis and molecular model

Abstract: Serine oligopeptidases of trypanosomatids are emerging as important virulence factors and therapeutic targets in trypanosome infections. A complete open reading frame of oligopeptidase B from Leishmania amazonensis was amplified with polymerase chain reaction with gradient annealing temperatures using primers designed for the oligopeptidase B gene from L. major. The 2,196-bp fragment coded for a protein of 731 amino acids with a predicted molecular mass of 83.49 KDa. The encoded protein (La_OpB) shares a 90% i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…As observed in T. cruzi, the results showed that the oligopetidase B-2 gene of L. amazonensis is expressed in both procyclic and metacyclic promastigotes and in axenic amastigotes suggesting that the gene is constitutively expressed throughout the life cycle of the parasite. The same results were observed with the oligopeptidase B gene of L. amazonensis (Guedes et al 2007) and with ITS region used as control (not shown).…”
Section: Phylogenetic Analysissupporting
confidence: 78%
See 2 more Smart Citations
“…As observed in T. cruzi, the results showed that the oligopetidase B-2 gene of L. amazonensis is expressed in both procyclic and metacyclic promastigotes and in axenic amastigotes suggesting that the gene is constitutively expressed throughout the life cycle of the parasite. The same results were observed with the oligopeptidase B gene of L. amazonensis (Guedes et al 2007) and with ITS region used as control (not shown).…”
Section: Phylogenetic Analysissupporting
confidence: 78%
“…(75%) is less than observed between oligopeptidases B-2 of T. cruzi and T. brucei (82%). Interestingly, oligopeptidases B-2 is more conserved than classical trypanosomatid oligopeptidases B (Guedes et al 2007). Sequence alignments with oligopeptidases B-2 from other trypanosomatids indicated conservation of the entire sequence with an absence of gaps (not shown).…”
Section: Sequence Alignment Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…From the sequencing of the L. major genome, a number of distinct serine proteases have been identified: (i) subtilisin-like, an S9 family member that also includes prolyloligopeptidase (POP), peptidyl-1 dipeptidase IV and oligopeptidase B (OPB), (ii) a type I signal peptidase (SPase I), (iii) a lysosomal serine carboxypeptidase, (iv) a 26S regulatory proteasome subunit, (v) a nucleoporin homolog and (vi) an orthologous of the rhomboid-like intramembranous serine peptidase family [12]. From the L. amazonensis genome, two others of interest are; (vii) Oligopeptidase B [13] and (viii) Oligopeptidase B2 [14].…”
Section: Introductionmentioning
confidence: 99%
“…Oligopetidase B, along with a new member called have been identified in L. amazonensis [13,14], however, their biological roles are unknown. Attempts to create null mutants of SPase I have been unsuccessful, suggesting that this enzyme is crucial to survival.…”
Section: Introductionmentioning
confidence: 99%